INCREASING COMMUNICATION AND CAPABILITY MATHEMATIC DISPOSITION OF SMA STUDENTS THROUGH EXPLORATION APPROACH - Wiwi Kartiwi; Utari Sumarmo; Asep Ikin Sugandi (IKIP Siliwangi, 2018)
This study is a quasi experimental research, which aims to examine the achievement and improvement of communication skills and creative thinking and mathematical disposition of high school students through an exploratory approach. The sample consists of 2 classes amounting to 68 students of class XI one high school in West Bandung. Instruments in this study are each set of test description of the ability of mathematical communication, and a set of mathematical disposition scale. The study found that the achievement of mathematical communication ability of high school students who received learning with exploratory approach is better than those who received regular learning reviewed in whole and the students' early mathematical ability. Likewise, the improvement of mathematical communication ability of high school students who received learning with better exploration approach than those who received regular learning reviewed in whole and early mathematical ability of their students. However, there was no interaction between the exploration approach and the students' early mathematical ability that resulted in communication skills and mathematical disposition students. For the achievement of mathematical disposition ability of students whose learning using exploratory approach is better than students with ordinary learning reviewed overall and early mathematical ability, but there is no interaction of exploration approach and KAM that resulted in mathematical disposition of students. Besides, there is also a considerable relation between communication ability and mathematical disposition of students.